Clinical factors associated with early disease progression after radioembolization for hepatocellular carcinoma and feasibility of post‐progression systemic therapy. Issue 3 (5th October 2022) - Van Laeken, Charlotte; Taelman, Thibault; Cappuyns, Sarah; Maleux, Geert; Vandecaveye, Vincent; Verslype, Chris; Deroose, Christophe; Dekervel, Jeroen
Abstract: Background and Aims: Radioembolization (RE) for unresectable hepatocellular carcinoma (HCC) can provide clinical benefit for well‐selected patients, whilst in others, rapid disease progression is observed. As an alternative for this patient population, new potent systemic treatment options are emerging. We aimed to identify the clinical factors associated with rapid progression following RE and assess the feasibility of starting a systemic treatment after progression. Methods: A retrospective cohort study of patients with unresectable HCC undergoing RE at a single referral centre between January 2009 and December 2018. Progression‐free and overall survival times were calculated. Uni‐ and multivariate cox regression analysis was used to assess factors associated with poor outcomes. Charts were reviewed for post‐progression treatment strategies. Results: Overall, 116 patients with unresectable HCC were included. Median PFS after RE was 6.7 months (95% CI 3.97–9.37), which varied significantly ( P  < .001) with Eastern Cooperative Oncology Group Performance Status (EGOC PS) (ECOG 0, 20.9 months [95% CI 8.6–33.2]; ECOG 1, 7.7 months [95% CI 3.1–12.1]; ECOG 2, 4.4 months [95% CI 1.7–7]). This association remained significant after multivariate testing, together with the number of HCC lesions ( P  = .017) and α‐FP ( P  = .050). Progressive disease after RE occurred in 82 patients, of whom only 40 received subsequent systemic treatment. Again, ECOG PS at the time of progression was significantly better for patients who did receive systemic treatment versus those who did not ( P  = .002). Conclusion: Patients with unresectable HCC, impaired general condition and multinodular disease have inferior outcomes after radioembolization. After RE, close monitoring of patient performance status, liver function and cancer control is warranted to allow timely initiation of systemic treatment when indicated. Abstract : More than two thirds of patients progressed after radioembolization, and half of them were not deemed suitable for systemic treatments. Therefore, after radioembolization, close monitoring of patient performance status, liver function and cancer control is warranted to allow timely initiation of systemic treatment options when indicated.